2020
DOI: 10.9734/ajmah/2020/v18i930240
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Pediococcus acidilactici Isolated from Wara, a Nigerian Milk Product, in the Prevention of Diarrhea and the Modulation of Intestinal Microflora in Wistar Rats

Abstract: Animals have been used in the evaluation of probiotic potentials of lactic acid bacteria for the development of functional food as only in-vitro tests may not be enough to ascertain the probiotic ability of an organism and its safety in a living host. The action of a probiotic Pediococcus acidilactici strain isolated from Wara, a Nigerian milk product, in the treatment of Diarrhea in wistar rats infected orally with Diarrhoeagenic Enterotoxigenic Escherichia coli as well as the survival and microflora modulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…If used in fermented meat products, it can significantly improve the texture and flavor of meat products (Jiang et al, 2023). It can also regulate intestinal flora and improve the immunity (Olajugbagbe et al, 2020). Moreover, P. pentosaceus can control foodborne pathogens, regulate intestinal microflora, reduce cholesterol, and so on.…”
Section: S Rdna Molecular Identification Resultsmentioning
confidence: 99%
“…If used in fermented meat products, it can significantly improve the texture and flavor of meat products (Jiang et al, 2023). It can also regulate intestinal flora and improve the immunity (Olajugbagbe et al, 2020). Moreover, P. pentosaceus can control foodborne pathogens, regulate intestinal microflora, reduce cholesterol, and so on.…”
Section: S Rdna Molecular Identification Resultsmentioning
confidence: 99%
“…SBT 2028 had the best antioxidant effects out of 570 strains of LAB (Kaizu et al, 1993) . 19 strains of LAB have antioxidant of 7-12 percent in intracellular cell-free extracts, due to their metal-ionchelating and ROS-scavenging capabilities (Lin and Yen, 1999), Olajugbagbe et al(2020) indicated that Pediococcus acidilactici isolated from Wara was able to act as a therapeutic agent against a Diarrhoeagenic Enterotoxigenic E. coli and improve gut health . Several scienti c studies have con rmed that the daily ingestion of probiotics or their related products, notably lactic acid bacteria, signi cantly improved human health through a variety of effects, including xenobiotic detoxi cation and competition with pathogenic microbial agents (Maurice et al, 2013), Silymarin is a common herbal extract used as a hepatoprotective agent a mixture of avonolignans obtained from milk thistle (Williamson et al, 1996) , In natural dietary sources, antioxidants are available, and the intake of antioxidants have a number of possible health bene ts (Yeung et al, 2019) .…”
Section: Introductionmentioning
confidence: 99%